Generalization of Mellin derivative and its applications. Issue 8 (2nd August 2016) - Kargın, Levent; Corcino, Roberto B.
ABSTRACT: In this paper we define generalized exponential polynomials by means of the generalization of the Mellin derivative ( x D ) . We give different proofs for some known results and obtain a new recurrence relation and a new operator formula for generalized exponential polynomials. We also define generalized geometric polynomials by means of the generalization of the Mellin derivative ( x D ) and obtain their basic properties.